Perlindungan Hukum Terhadap Hak Pekerja Atas Perolehan Jaminan Sosial Tenaga Kerja - Muhammad Zainuddin (Fakultas Hukum Universitas Mataram, 2016)
Social security is a right of everyone, without exception, including workers / laborers as the provisions of Article 28H paragraph (3) of the Constitution of 1945, which reads;